Research and progress of cGAS/STING/NLRP3 signaling pathway: a mini review - Chen, Ke-qian; Tang, Wen-rui; Liu, Xiang (Frontiers in Immunology, 2025)
Over the past decade, inflammasome and cGAS-STING have received significant attention as immune components that coordinate host immune homeostasis. Although the inflammasome and cGAS-STING are relatively independent immune signaling pathways, some studies have pointed out that there is an important association between cGAS-STING and the inflammasome. As the downstream of cGAS-STING, inflammasome plays an important role in many diseases. In this mini-review, we review the association between CGAS-STING and NLRP3 inflammasome, the progression of the cGAS/STING/NLRP3 signaling pathway in the pathogenesis of disease, the therapeutic strategies that targeted cGAS/STING/NLRP3 signaling pathway. We believe that targeting the cGAS/STING/NLRP3 signaling pathway in the future has broad prospects and significance for the treatment of disease.